Media Permainan Jumanji FlashCard untuk Pembelajaran Fisika SMP Materi Pengukuran - Laspri Tri Marheny; Lukman Hakim; Sulistiawati Sulistiawati (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
This study aimed to develop a Jumanji flashcard game media for valid and practical media. Research and development methods are used in this study. The research phase starts from potential and problem analysis, data collection phase, product design phase, design validation phase, design revision phase, trial and product revision phase. Interview sheets, questionnaires and documentation obtained research data. Data collection techniques used interview sheets, material expert validation questionnaires, media expert questionnaires and student response questionnaires. The results obtained are the feasibility of the Jumanji flashcard game based on the assessment of material experts with a percentage of 88.67%, media experts 90%, and student responses 92% in the small group trial obtained very good category. Aspects of material validation consist of accuracy, depth and completeness of the material. Aspects of media expert validation consist of function, design and quality of media. Student responses related to the practice of the Jumanji flashcard game media. The Jumanji flashcard game media developed was feasible and could be used in physics learning for junior high school students for measurement.